Analysis of Regional Clusters in Indonesia based on Factors Causing Stunting using Self Organizing Map Algorithm - Karyati; Bellapurani, Larrachita Rizka (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
This study aimed to classify regions in Indonesia based on the causes of stunting which are included in specific intervention and sensitive intervention framework, so that related parties can use them to address the biggest causal factors in each region. This research used the Self Organizing Map (SOM) method. The variables used were the percentage of children aged less than 6 months who were exclusively breastfed, the percentage of children aged 12-23 months who received complete basic immunization, the percentage of ever-married women aged 15-49 years whose last birth was facilitated by health workers and assisted by health workers, the percentage of households that have access to proper drinking water sources, and the percentage of households that have access to proper sanitation. The results obtained 6 clusters with their respective characteristics. Cluster 1 consists of 27 districts/cities, cluster 2 consists of 59 districts/cities, cluster 3 consists of 23 districts/cities, cluster 4 consists of 264 districts/cities, cluster 5 consists of 103 districts/cities and cluster 6 consists of 38 districts/cities.